Anomalous Seismicity Patterns Study of Three Mainshocks Occurred in Arakan-yoma Region - Panthi, Ananta (Himalayan Physics, 2013)
The anomalous seismic activity prior to three mainshocks occurred in Arakan-yoma region, within the area bounded by 20o-28o N and 92o-98o E, has been studied considering spatial distribution and temporal patterns of earthquakes. The anomalous seismic activity has been investigated in this region using the seismicity data for the period 1963 to 2008 with events having magnitude mb ≥ 4.3. From the study, it has been inferred that all three mainshocks occurred in Arakan-yoma region were well preceded by anomalous seismicity pattern. The Himalayan Physics Vol. 4, No. 4, 2013 Page: 34-39 Uploaded date: 12/23/2013